Human transforming growth factor α (TGF-α) is digested to a smaller (1–43), less biologically active, form in acidic gastric juice. (1st December 2002) - Marchbank, T; Boulton, R; Hansen, H; Playford, R J
Abstract : Background: Transforming growth factor α (TGF-α) is a 50 amino acid peptide with potent proliferative and cytoprotective activity present in gastric mucosa and juice. Aims: To determine the forms and biological activity of natural and recombinant TGF-α following incubation with acid pepsin. Patients: Human gastric juice was obtained under basal conditions from patients taking acid suppressants and from volunteers undergoing intragastric neutralisation. Methods: Samples were analysed using mass spectroscopy and/or high pressure liquid chromatography with radioimmunoassay. Biological activity was determined using thymidine incorporation into rat hepatocytes and an indomethacin/restraint induced gastric damage rat model. Results: TGF-α1–50 is cleaved to TGF-α1–43 by acid pepsin and this is the predominant form in normal gastric juice. However, intragastric neutralisation or taking acid suppressants caused the predominant form to be TGF-α1–50 . TGF-α1–43 had only half of the ability to maximally stimulate [ 3 H]thymidine incorporation into primary rat hepatocytes (28 177 (1130) DPM/well for 2.16 nM TGF-α1–43 v 63 184 (3536) DPM/well for TGF-α1–50 ; p<0.001). A similar reduced potency was seen when used in an indomethacin induced rat gastric damage model (0.18 μmol/kg/h of TGF-α1–43 reduced ulcer area by 19% whereas TGF-α1–50 reduced area by 62%; p<0.001). Conclusions: TGF-α1–50 is cleaved to the TGF-α1–43 form by acid pepsin, causing 2–5-fold loss of biological activity. Such changes may have relevance to the actions of acid suppressants and the importance of this peptide in both normal and abnormal growth.